Field manual of diseases on trees and shrubs - Horst, R. Kenneth , 1935- (Life sciences, 2013)
The Trees and Shrubs manual is a reference manual on diseases which attack trees, shrubs, and vines. The manual identifies various types of diseases which are known to invade these plants located throughout North, Central, and South America. The recordings include diseases caused by fungi, bacteria, viruses, viroids, phytoplasmas, and nematodes. Causal disease agents are described and illustrated in some cases and diseases and disease control measures are also discussed. A manual such as this is never finished since new reports of diseases are continuously reported. Periodicals that are regularly reviewed include Plant Disease, Phytopathology, Review of Applied Mycology, Journal of Economic Entomology, Arborist's News, and Proceedings of the National Shade Conference